Design and simulation of a novel 3-point star rectifying antenna for RF energy harvesting at 2.4 GHz. Issue 1 (1st January 2021) - Olowoleni, J. O; Awosope, C. O. A; Adoghe, A. U; Obinna, Okoyeigbo; Ebubechukwu Udo, Udochukwu
Abstract: The rectenna as a device, is critical for achieving long-distance wireless power transfer. The centrality of this study is focused on adding to the collective knowledge of the subject matter, by providing a new perspective in terms of an alternative design for the antenna component of the rectenna. Essentially, this study features a novel "3-point star" design which was simulated in comparison with the conventional square microstrip patch antenna design. Both designs (i.e., operating at the Wi-Fi band 2.4 GHz), were assessed in terms of simulated performance parameters: gain, directivity, return loss, radiation pattern, and efficiency. From the simulation results, the proposed "3-point star" design, though slightly less efficient exhibited improved performance over the conventional square patch alternative, in terms of gain, directivity, and return loss. For the rectifying component, a greinacher voltage-doubler (with two HSMS2820 diodes), was designed separately and simulated over a range of input power levels (10dBm—34dBm), for 220-Ω, 380-Ω and 810-Ω load resistances, respectively. A maximum conversion efficiency of 88.02% was achieved at 28dBm for an 810 Ω load resistance. All design simulations were executed using Advanced Design System (ADS) software.